High-throughput screens identify HSP90 inhibitors as potent therapeutics that target inter-related growth and survival pathways in advanced prostate cancer. Issue 1 (December 2018) - Jansson, Keith; Tucker, John; Stahl, Lauren; Simmons, John; Fuller, Caitlyn; Beshiri, Michael; Agarwal, Supreet; Fang, Lei; Hynes, Paul; Alilin, Aian; Lake, Ross; Abbey, Yasmine; et al.
Abstract The development of new treatments for castrate resistant prostate cancer (CRPC) must address such challenges as intrinsic tumor heterogeneity and phenotypic plasticity. CombinedPTEN/ TP53 alterations represent a major genotype of CRPC (25–30%) and are associated with poor outcomes. Using tumor-derived, castration-resistantPten/Tp53 null luminal prostate cells for comprehensive, high-throughput, mechanism-based screening, we identified several vulnerabilities among >1900 compounds, including inhibitors of: PI3K/AKT/mTOR, the proteasome, the cell cycle, heat shock proteins, DNA repair, NFκB, MAPK, and epigenetic modifiers. HSP90 inhibitors were one of the most active compound classes in the screen and have clinical potential for use in drug combinations to enhance efficacy and delay the development of resistance. To inform future design of rational drug combinations, we tested ganetespib, a potent second-generation HSP90 inhibitor, as a single agent in multiple CRPC genotypes and phenotypes. Ganetespib decreased growth of endogenousPten/Tp53 null tumors, confirming therapeutic activityin situ . Fifteen human CRPC LuCaP PDX-derived organoid models were assayed for responses to 110 drugs, and HSP90 inhibitors (ganetespib and onalespib) were among the select group of drugs (<10%) that demonstrated broad activity (>75% of models) at high potency (IC50 <1 µM). Ganetespib inhibits multiple targets, including AR and PI3K pathways, which regulate mutually compensatory growth and survival signals in some forms of CRPC. Combined with castration, ganetespib displayed deeper PDX tumor regressions and delayed castration resistance relative to either monotherapy. In all, comprehensive data from near-patient models presents novel contexts for HSP90 inhibition in multiple CRPC genotypes and phenotypes, expands upon HSP90 inhibitors as simultaneous inhibitors of oncogenic signaling and resistance mechanisms, and suggests utility for combined HSP90/AR inhibition in CRPC.